TINDAK PIDANA ZINA MENURUT UU NO 1 TAHUN 1946, UU NO 1 TAHUN 2023 (KUHP) DAN HUKUM ISLAM - Nasruddin S; Achmad Nurdaim (INTELIGENSIA MEDIA, 2023)
This study conducts a comparative analysis of zina offenses across the Criminal Code, both the old legislation and the recent amendments (Law No. 1 of 2023), and Islamic law. Employing a juridical normative approach, the research involves the examination of primary and secondary data, including legal literature. According to the old Criminal Code, individuals engaged in adultery while married or legally bound by marriage face a maximum penalty of nine months in prison. In the current Islamic penal code, adultery is categorized into two cases: muhsan offenders are subject to stoning to death, while ghairu muhsan offenders receive a hundred lashes and one year of exile. Notably, both the old and new Criminal Codes extend the scope to include adulterers, whether single or married. The charge for adultery in both codes remains the same, with the new code expanding the range of complainants to include in-laws, parents, and children—whereas, in the old code, only the spouse could file a complaint. Islamic Law classifies zina as a jarimah hudud, with sanctions deemed solely under Allah's jurisdiction. The current criminal sanctions in the Criminal Code are perceived as insufficiently stringent, necessitating prompt legislative revisions for more robust and deterrent measures against adulterers.